(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The implementation of control tests is an assisting factor for the auditor in determining the level of compliance with the elements included in the internal control system, which helps the auditor in the initial evaluation process and then reaching the final evaluation of the system to estimate the size of the essential tests to be designed by the auditor. Among the most important results, there is an effect of reducing the auditing profession’s risks in improving the audit’s quality. Effective and appropriate planning is important and contributes significantly to reducing audit risks in the auditors’ report through its contribution to understanding the unit’s scope of work and activity, identifying risk areas, and the extent to which unit continuity is possible. Among the most important recommendations is to urge auditors in the public and private sectors to increase cooperation between them by holding workshops for academics specialized in the field of accounting and auditing optimally, improving the performance of the economic unit’s work as a whole, and creating and enhancing the added value of the economic unit and reducing its risks that affect the quality of auditing. Furthermore, work to link the audit and internal control department with the company’s board of directors, which provides a degree of organizational independence according to the international standards for auditing ISA Standard 1110, thus guarantees the objectivity of the opinion presented.